Modeling of Production Strategies from Common Offshore Gas Field with Game Theory Approach - Seyed Pendar Toufighi; Mohamadreza Mehregan; Ahmad Jafarnejad (Mathematics Interdisciplinary Research, 2022)
Common oil and gas fields are among the most valuable income and national wealth sources, so production delays cause irreparable damage to the national economy. The existing functions of revenues and production costs of gas fields have been identified and extracted from the current literature to optimize the production strategy. Cost func-tions include exploration, development, operation, production facility and wellhead, facility depreciation costs, and revenue functions include demand and income functions. After designing the model using mathematical optimiza-tion, the decision variables’ values have been calculated as optimal production, selling price, and profit for each play-er. For this purpose, two strategies of cooperation and non-cooperation were considered for each player. Solving the designed games showed that the best strategy and Nash equilibrium for the research case study is the strategy of co-operation. Also, according to the results of the equilibrium of designed games based on cooperation strategy, it is suggested that one of the main approaches of research case study in common fields is the process of multilateral and cooperative development.